2010
DOI: 10.1212/wnl.0b013e3181fc27e4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy biomarkers in premanifest and early Huntington disease

Abstract: Objectives: To evaluate in vivo brain metabolite differences in control subjects, individuals with premanifest Huntington disease (pre-HD), and individuals with early HD using 1 H magnetic resonance spectroscopy (MRS) and to assess their relationship with motor performance.Methods: Eighty-five participants (30 controls, 25 pre-HD, and 30 early HD) were recruited as part of the TRACK-HD study. Eighty-four were scanned at 3 T with single-voxel spectroscopy in the left putamen. Disease burden score was Ͼ220 among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 38 publications
9
102
2
3
Order By: Relevance
“…Both Cr and PCr increased in striatum and cortex, suggesting that additional disease-related mechanisms beyond energy balance were perturbing their steady-state levels. In contrast to the current study, total creatine was reported to decrease beginning at presymptomatic stages in humans (Sturrock et al, 2010). The observed increase in cortical Lac was not present in the previous study (Tkac et al, 2007) but changes in Lac, both increases and decreases, have been noted by others (Jenkins et al, 2005;Tsang et al, 2006).…”
Section: Metabolite Changes Reliably Anticipated Volume Changescontrasting
confidence: 99%
See 2 more Smart Citations
“…Both Cr and PCr increased in striatum and cortex, suggesting that additional disease-related mechanisms beyond energy balance were perturbing their steady-state levels. In contrast to the current study, total creatine was reported to decrease beginning at presymptomatic stages in humans (Sturrock et al, 2010). The observed increase in cortical Lac was not present in the previous study (Tkac et al, 2007) but changes in Lac, both increases and decreases, have been noted by others (Jenkins et al, 2005;Tsang et al, 2006).…”
Section: Metabolite Changes Reliably Anticipated Volume Changescontrasting
confidence: 99%
“…Elevated myo-Ins, principally found within astrocytes, is considered a marker for gliosis and is elevated in a number of neurodegenerative diseases (Fisher et al, 2002;Oz et al, 2010a). Similarly, increases in myo-Ins and decreases in NAA have been found in both R6/2 mice and presymptomatic and early stage HD patients (Jenkins et al, 2005;Tsang et al, 2006;Sturrock et al, 2010). In the human 3T MRS study, choline increased in early stage HD, consistent with the mouse data (Sturrock et al, 2010).…”
Section: Metabolite Changes Reliably Anticipated Volume Changessupporting
confidence: 75%
See 1 more Smart Citation
“…PET studies of Huntington's patients without hyperactive behavior have shown frontal metabolism to be normal but with decreased caudate and putamen metabolism [49,50]. However is it thought that normal frontal metabolism in Huntington's may result from a coexistent neurological degeneration and the resultant thalamo-frontal hyper-stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Lower neuronal markers (N-acetylaspartate) levels were shown in presymptomatic and early HD, whereas glial cell markers (myo-inositol) were increased (Surrock et al 2010). Elevated lactate and reduced creatine levels were shown in the striatum of presymptomatic HD gene carriers and early HD patients (Reynolds et al 2005).…”
Section: Molecular Mri Techniquesmentioning
confidence: 95%